2013
DOI: 10.1111/acps.12144
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary treatment of schizophrenia patients 2004–2010 in Denmark

Abstract: Involuntary treatment involved a wide range of somatic treatment. Antipsychotic medicine was the most common psychotropic used. Involuntary treatment with depot antipsychotics and clozapine were rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Another survey found that approximately 40% of psychiatrists did not attempt switching patients from APP to antipsychotic monotherapy . Since clozapine is a more evidence-based treatment option than APP, more should be done to ensure that treatment follows treatment guidelines and clozapine should be attempted before using APP if used to target poor therapeutic response (Andersen et al, 2014). More should be done to equip psychiatrists on how to switch from APP to antipsychotic monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another survey found that approximately 40% of psychiatrists did not attempt switching patients from APP to antipsychotic monotherapy . Since clozapine is a more evidence-based treatment option than APP, more should be done to ensure that treatment follows treatment guidelines and clozapine should be attempted before using APP if used to target poor therapeutic response (Andersen et al, 2014). More should be done to equip psychiatrists on how to switch from APP to antipsychotic monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This study used the assumption that patients did not have any symptoms of MI because they did not receive treatment. However, some patients may have had symptoms but did not seek treatment because they may have been afraid of using the healthcare system – for example, due to risk of involuntary admission (28). On the other hand, patients with schizophrenia may have experienced the symptoms but interpreted them in a psychotic context, such as radiation from outer space.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 39 British psychiatrists, 6 reported enforcing intramuscular medication each time oral clozapine was refused [ 11 ]. In a register-based study from Denmark, it was reported that 2 patients with schizophrenia were receiving intramuscular clozapine involuntarily during a studied period [ 37 ].…”
Section: Reviewmentioning
confidence: 99%